Syeikh Muhammad Arsyad Al-Banjary and the Tradition of Pengajian Langgar in South Kalimantan - Malisi, M. Ali Sibram; Azis, Abdul; Asmawati, Asmawati; Supriadi, Gito; Rahmawati, Laila (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
This article investigates the continuous social history of Pengajian Langgar in South Kalimantan, initiated by Shaikh Muhammad Arsyad al-Banjary and his descendants until the present day. This research is important because Pengajian in South Kalimantan, until today, remains maintaining its tradition. This study used literature and interviews as methods. The paper finds that the spread of Islamic teachings from Mecca officially began in the mid-18th century. His pioneering was Shaikh Muhammad Arsyad Al-Banjary (1122-1227 H./1710 – 1812 M.). These are the scholars who developed the pengajian system in South Kalimantan. Pengajian is a system of teaching that disseminates the teachings of Islam in this area at the beginning of the residence of the scholars concerned. However, many are taking place in Langgar. Until 1920, in almost every langgar, Tuan Guru provided themselves to conduct Pengajian in this area.